DEVELOPMENT OF AN IMPROVED PEDAL POWERED WASHING MACHINE - Mogaji, P B; Jayeola, H O; Echoga, D A (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2020)
This research work deals with the design and fabrication of an improved cloth washing machine capable of small-scale industrial applications as well as household use. The project is aimed at developing a washing machine that is efficient, affordable, durable and compatible for rural areas with little or no supply of electricity; by working on the efficiencies of pre-developed machines and providing solutions to their deficiencies; a dynapod with gear-sprocket system combined with the belt-pulley system is used to transmit torque via leg cranking to the shaft of the washing drum (agitator in an electric washing machine); the dynapod is also used to vary (increase or decrease) the speed of the machine to facilitate different speeds for the three main operations in laundry process washing, rinsing, and spinning which are the three main operations of the washing machine, speed is further increased with the aid of the belt-pulley system. With an overall efficiency of 84.98%, the cost of fabricating the machine is 45,000NGN (123.80USD) and this can be significantly reduced if produced in a large scale. The machine is easy to use and maintain as the system of operation is simple, it is eco-friendly and safe for the user. The machine is capable of community application therefore can be used by the entire populace of a rural area or settlement.